Illustrated guide to astronomical wonders - Thompson, Robert Bruce (Make:Books, 2007)
"With capable, high quality telescopes now available for as little as USD250, amateur astronomy is really taking off. If you want to join the fun, this is the ideal book to get you started. The Illustrated Guide to Astronomical Wonders explains the equipment you need right away, and describes how and where to find hundreds of spectacular objects in the night sky - beautiful multiple stars, spectacular star clusters, nebulae, galaxies, and more." "This book is perfect for amateur astronomers, students, teachers, or anyone who's ready to dive into this rewarding hobby. Designed to be read in the field under red lighting used by astronomers to preserve night vision, the Illustrated Guide to Astronomical Wonders includes recommended observing targets for beginners and intermediate stargazers alike." "Discover what awaits you in the night sky. Who knows? Maybe you'll find a new object. On a clear cold night in January 2004, amateur astronomer Jay McNeil spotted an undiscovered celestial object near Orion, now called McNeil's Nebula."--Jacket
Print version record
Keywords: Astronomy -- Observers' manuals; Constellations -- Observers' manuals; Constellations; Manuels d'observation; NATURE; Sky Observation; Astronomy; Constellations; Handbooks and manuals